Aunt Jane's Nieces at Work - Baum, L. Frank (Saga Egmont, 2021)
First published in 1909, ‘Aunt Jane’s Nieces at Work’ is the fourth book in the ‘Aunt Jane’ series by author L. Frank Baum. Louise, Elizabeth and Patsy hear that their friend Kenneth Forbes is running for the state legislature and is worried that he might lose. Though unable to vote in elections themselves at this time, the young women nonetheless prove themselves to be a formidable force; canvassing for votes, uncovering underhand dealings, and fighting corrupt politicians as they come to Kenneth’s aid.